Cognitive Analysis of the Understanding of Euclidean Geometry Concepts of Students in the Mathematics Education Study Program - Huda, Ristianur (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to conduct a cognitive analysis of mathematics education students' understanding of concepts in Euclidean geometry. Students are often unable to fully achieve and optimize the formal cognitive stages required in Euclidean geometry, resulting in a gap between the complex structure of the material and their thinking abilities. This is a descriptive qualitative study aimed at examining students' cognitive processes. The subjects were 11 second-semester Mathematics Education students who had taken the Euclidean Geometry course in the even semester of the 2024/2025 academic year. The main instrument was a Euclidean geometry comprehension test supported by a questionnaire to explore thinking processes and misconceptions. Evaluation of understanding was reviewed based on the cognitive level. The results showed that many students, even at the tertiary level, were still at a low level in the Van Hiele framework, namely level 0 (Visualization) or level 1 (Analysis). This condition causes students to tend to experience difficulties in conducting formal proofs; 63.6% of students lacked understanding due to a low logical understanding of Euclidean postulates. The level of students' understanding of Euclidean geometry is strongly influenced by how they process information cognitively. Therefore, teachers need to develop structured learning strategies based on Van Hiele's learning phases to facilitate students' cognitive progress in a gradual and planned manner.